PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI INDONESIA - Fenia Pranilsa; Hana Yuli Sartika; Aura Monalisa; Yuli Ahmadi Yanti; Marina Selfina Monika; Kartini Putri Dewi (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
Based on the observation that not many studies have explained the role of school principals in improving the quality of education. Even though research on the role of school principals in improving the quality of education is important. Based on these observations, research will be conducted on the role of school principals in improving the quality of education. This research method uses qualitative methods with the type of literature study. The role of the principal in improving the quality of education is that the principal acts as an educator, the principal acts as a manager, the principal acts as an administrator, the principal acts as a supervisor, and the principal acts as an entrepreneur.